1990
DOI: 10.1111/j.1754-4505.1990.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system for the quantitative evaluation of oral mucositis during bone marrow transplantation

Abstract: A system for assessing the severity of mucositis in patients undergoing bone marrow transplantation (BMT) is presented. Ten criteria were graded to give component scores together with a total score. The overall severity score ranged from 0 through 21. Scores were assigned three times daily by nursing staff members and verified daily by the attending dental and medical practitioners. Total scores were highly reproducible and were related to the severity of neutropenia. Variation between sequential total scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
0
13
1
Order By: Relevance
“…This fact confirms the methodologic option for the use of OMAS. These results support OMAS as an instrument capable of portraying the clinical 25 Although a delay in the start of OM was expected in patients from the laser group, a significant statistical difference between the laser and control groups was not observed, and this result deserves further investigation. Further, no significant statistical difference was seen between the laser and control groups in the total time with OM.…”
Section: Discussioncontrasting
confidence: 57%
“…This fact confirms the methodologic option for the use of OMAS. These results support OMAS as an instrument capable of portraying the clinical 25 Although a delay in the start of OM was expected in patients from the laser group, a significant statistical difference between the laser and control groups was not observed, and this result deserves further investigation. Further, no significant statistical difference was seen between the laser and control groups in the total time with OM.…”
Section: Discussioncontrasting
confidence: 57%
“…The study observed 31 adult patients undergoing BMT, which included one 13-year-old patient. Staff had been trained to score mucositis by senior staff members and reliability testing was limited to reproducibility analysis of the variation in mucositis scores by different nursing staff members [41]. Validity was not examined.…”
Section: Development and Evaluation Of Oral Assessment Toolsmentioning
confidence: 99%
“…Validation was not examined. Similarly, another combined scale, the Walsh Scale, evaluated ten separate categories that were scored on a 3-or 4-point severity scale [41]. The study observed 31 adult patients undergoing BMT, which included one 13-year-old patient.…”
Section: Development and Evaluation Of Oral Assessment Toolsmentioning
confidence: 99%
“…For example, the Walsh Scale gives a patient with a moist mouth the lowest score (0) and a dry mouth the highest score of 2 [32], where higher scores indicate increased severity of oral mucositis. It was the experience of the participants that children with mucositis more frequently suffered from drooling or pooling of saliva rather than a dry mouth.…”
Section: Functionmentioning
confidence: 99%